UOS molecular sieve and its preparation method and application and UOS molecular sieve composition and its application
Through the chemical composition and crystallization reaction of SiO2·1/x GeO2, UOS molecular sieve with high catalytic activity was prepared, which solved the problem of expensive template agents and narrow synthesis range in the prior art, and achieved high efficiency and low cost of UOS molecular sieve Preparation and multifunctional catalytic applications.
Patent Information
- Application Number
- CN202111233259.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-10-22
AI Technical Summary
In the existing UOS molecular sieve synthesis methods, template agents are expensive and have a narrow synthesis range, which limits their wide application.
Using the chemical composition of SiO2·1/x GeO2, the non-silicon tetravalent skeleton elements and trivalent skeleton elements are mixed with silicon source, germanium source, fluorine source and structural guide agent for crystallization reaction, and a sheet-like morphology is prepared. and high catalytically active UOS molecular sieve simplify the template agent structure and synthesis process and reduce costs.
It realizes the efficient preparation of UOS molecular sieve, has a high specific surface area and micropore volume, is suitable for different catalytic reactions, meets a variety of application needs, and reduces the synthesis cost.
Smart Images

Figure CN116002703B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieves, and in particular to a UOS molecular sieve and a preparation method and application thereof, and a UOS molecular sieve composition and application thereof. Background Art
[0002] Zeolite molecular sieve is a type of porous crystalline material with a regular molecular size pore structure, strong acidity and high hydrothermal stability. It is widely used in catalysis, adsorption and ion exchange and plays an irreplaceable role.
[0003] UOS molecular sieve is a mesoporous molecular sieve with three-dimensional cross channels, in which the 10-membered ring channel along the a-axis has an opening diameter of 0.36×0.63nm, and the opening diameters of the 8-membered ring channel along the b-axis and c-axis are 0.27×0.35nm and 0.30×0.30nm respectively. The unique channel system of UOS molecular sieve makes it have great application prospects in the fields of adsorption separation and catalytic conversion of organic matter. Researchers from the French Petroleum Research Institute first disclosed the structure and preparation method of UOS molecular sieve in French patent FR07 / 05.315. The template used in the synthesis is 3-ethyl-1-methylimidazolium ion (3-Ethyl-1-methyl-3H-imidazol-1-ium). The main problem of this synthesis method is that the template is expensive and the synthesis range of UOS molecular sieve is narrow. Summary of the invention
[0004] The purpose of the present invention is to provide a UOS molecular sieve and a preparation method and application thereof. The UOS molecular sieve has the advantages of simple organic template structure, simple preparation method and low synthesis cost.
[0005] In order to achieve the above-mentioned purpose, the present invention provides a UOS molecular sieve on the one hand, wherein the UOS molecular sieve has a schematic chemical composition as shown in the formula "SiO2·1 / x GeO2", wherein the molar ratio of SiO2 to GeO2 is 0.5≤x≤5, preferably the molar ratio of SiO2 to GeO2 is 1≤x≤4, and the UOS molecular sieve has a flaky morphology.
[0006] Preferably, the sheet thickness of the UOS molecular sieve is 20 to 500 nm.
[0007] Preferably, the physicochemical parameters of the UOS molecular sieve include: a specific surface area greater than 200 m 2 / g, micropore volume greater than 0.07cm 3 / g.
[0008] Preferably, the X-ray diffraction pattern of the UOS molecular sieve includes characteristic peaks as shown in the following table:
[0009]
[0010] Preferably, no more than 10 wt% of Si atoms in the UOS molecular sieve are substituted by at least one non-silicon tetravalent framework element Y.
[0011] Preferably, Y is selected from at least one of tin, titanium, zirconium and hafnium.
[0012] Preferably, 1 to 9 wt% of Si atoms in the UOS molecular sieve are replaced by at least one non-silicon tetravalent framework element Y.
[0013] Preferably, no more than 2 wt% of the Ge atoms in the UOS molecular sieve are substituted by at least one trivalent framework element X.
[0014] Preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
[0015] 0.2-1 wt% of Ge atoms in the UOS molecular sieve are replaced by at least one trivalent framework element X.
[0016] The second aspect of the present invention provides a method for preparing the UOS molecular sieve of the present invention, the method comprising:
[0017] A step of mixing an optional non-silicon tetravalent framework element Y source and / or a trivalent framework element X source, a silicon source, a germanium source, a fluorine source, a structure directing agent R and water to perform a crystallization reaction to obtain a UOS molecular sieve, wherein the structure directing agent R is 3-diethylamino-1-propanol;
[0018] The molar ratio of the silicon source calculated as SiO2 to the germanium source calculated as GeO2 is SiO2:GeO2=1:0.2~2, preferably SiO2:GeO2=1:0.25~1.
[0019] Preferably, the molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0 to 0.1, preferably 0.01 to 0.09.
[0020] Preferably, Y is selected from at least one of tin, titanium, zirconium and hafnium.
[0021] Preferably, the molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.01, preferably 0.001-0.005.
[0022] Preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
[0023] Preferably, the molar ratio of the structure directing agent R, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is R:SiO2:GeO2:F:H2O=0.15~4:1:0.2~2:0.2~4:12~45.
[0024] Preferred R:SiO2:GeO2:F:H2O=0.5~2:1:0.25~1:0.35~2.5:15~30.
[0025] Preferably, the silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane.
[0026] Preferably, the germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium.
[0027] Preferably, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride, preferably at least one of hydrofluoric acid and ammonium fluoride.
[0028] Preferably, the conditions of the crystallization reaction include: crystallization at 100-200° C. for 24-300 hours.
[0029] Preferably, the crystallization is carried out at 110 to 190° C. for 36 to 250 hours.
[0030] Preferably, the crystallization is performed under static conditions.
[0031] A third aspect of the present invention provides a UOS molecular sieve composition, which comprises the UOS molecular sieve described in the present invention and a binder.
[0032] A fourth aspect of the present invention provides a use of the UOS molecular sieve or the UOS molecular sieve composition of the present invention as an adsorbent or catalyst component.
[0033] The UOS molecular sieve of the present invention and its preparation method have the advantages of simple organic template structure and simple preparation method. After partially replacing Si and Ge elements in the framework, the UOS molecular sieve can also introduce one or more other framework elements (such as non-silicon tetravalent framework elements and / or trivalent framework elements) other than Si and Ge into the framework to produce different catalytic active centers to meet the needs of different catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the X-ray diffraction (XRD) pattern of the sample obtained in Example 1;
[0035] Figure 2This is a scanning electron microscope (SEM) image of the sample obtained in Example 1;
[0036] Figure 3 is the nitrogen adsorption-desorption isotherm of the sample obtained in Example 1;
[0037] Figure 4 is the X-ray diffraction (XRD) pattern of the sample obtained in Example 2;
[0038] Figure 5 This is a scanning electron microscope (SEM) image of the sample obtained in Example 2. DETAILED DESCRIPTION
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] On one hand, the present invention provides a UOS molecular sieve having a schematic chemical composition as shown in the formula "SiO2·1 / x GeO2", wherein the molar ratio of SiO2 to GeO2 is 0.5≤x≤5, preferably the molar ratio of SiO2 to GeO2 is 1≤x≤4, and the UOS molecular sieve has a flaky morphology.
[0041] According to a preferred embodiment of the present invention, the sheet thickness of the UOS molecular sieve is 20 to 500 nm.
[0042] According to a preferred embodiment of the present invention, the physicochemical parameters of the UOS molecular sieve include: a specific surface area greater than 200 m 2 / g, micropore volume greater than 0.07cm 3 / g.
[0043] According to a preferred embodiment of the present invention, the X-ray diffraction spectrum of the UOS molecular sieve includes characteristic peaks as shown in the following table:
[0044]
[0045]
[0046] In the present invention, in the X-ray diffraction pattern, vw, w, m, s, and vs represent the diffraction peak intensity, vw is very weak, w is weak, m is medium, s is strong, and vs is very strong; generally speaking, vw is less than 5%, w is 5%-20%, m is 20%-40% (including 20% and 40%), s is 40%-70%, and vs is greater than 70% (including 70%).
[0047] Since the strength is affected by many factors, the data in the above table are expressed as the interplanar spacing of UOS molecular sieve at 2θ(°) of 7.68±0.2. It is 11.50±0.55, and the relative intensity (%) (I / I0)×100 is vw-w (0-20%), and so on. The technical personnel in this field are well aware of the representation method of the table, and the present invention will not explain them one by one here.
[0048] According to the present invention, after partially replacing the Si and Ge elements in the framework of the UOS molecular sieve, one or more other framework elements (such as non-silicon tetravalent framework elements and / or trivalent framework elements) other than Si and Ge can be introduced into the framework to produce different catalytic active centers to meet the needs of different catalytic reactions.
[0049] According to a preferred embodiment of the present invention, no more than 10wt% of Si atoms in the UOS molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y; preferably, the Y is selected from at least one of tin, titanium, zirconium and hafnium. In the examples, titanium is used as an example, but the present invention is not limited to this scope.
[0050] According to a preferred embodiment of the present invention, 1-9 wt% of Si atoms in the UOS molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y.
[0051] According to a preferred embodiment of the present invention, no more than 2wt% of Ge atoms in the UOS molecular sieve are replaced by at least one trivalent skeleton element X; preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium. In the examples, aluminum is used as an example, but the present invention is not limited to this scope.
[0052] According to a preferred embodiment of the present invention, 0.2-1 wt% of Ge atoms in the UOS molecular sieve are replaced by at least one trivalent framework element X.
[0053] The UOS molecular sieves having the above characteristics can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the second aspect of the present invention, the present invention provides a method for preparing the UOS molecular sieve of the present invention, the method comprising:
[0054] A step of mixing an optional non-silicon tetravalent framework element Y source and / or a trivalent framework element X source, a silicon source, a germanium source, a fluorine source, a structure directing agent R and water to perform a crystallization reaction to obtain a UOS molecular sieve, wherein the structure directing agent R is 3-diethylamino-1-propanol;
[0055] The molar ratio of the silicon source calculated as SiO2 to the germanium source calculated as GeO2 is SiO2:GeO2=1:0.2-2, preferably SiO2:GeO2=1:0.25-1. The preparation method has the advantages of simple organic template structure and simple preparation method.
[0056] According to a preferred embodiment of the present invention, the molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0-0.1, preferably 0.01-0.09; preferably, the Y is selected from at least one of tin, titanium, zirconium and hafnium;
[0057] According to a preferred embodiment of the present invention, the tin source is selected from at least one of tin tetrachloride, stannous chloride, alkyl tin, alkoxy tin and organic tin esters; the titanium source is selected from at least one of tetraalkyl titanates (such as tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetra-n-butyl titanate), titanium tetrachloride, hexafluorotitanic acid, titanium sulfate and their hydrolyzates; the zirconium source and hafnium source are selected from conventional substances in the art, such as zirconium nitrate, zirconium oxychloride, hafnium sulfate, etc.
[0058] According to a preferred embodiment of the present invention, the molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.01, preferably 0.001-0.005; preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
[0059] According to a preferred embodiment of the present invention, the aluminum source is selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, aluminum oxide, aluminum hydroxide, silica-aluminum zeolite molecular sieve, aluminum carbonate, elemental aluminum, aluminum isopropoxide and aluminum acetate; the boron source is selected from at least one of boric acid, sodium tetraborate, amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate and organic boron esters; the iron source is selected from at least one of ferric sulfate, ferric nitrate, iron halide (such as ferric chloride), ferrocene and ferric citrate; the gallium source, indium source and chromium source are selected from conventional substances in the art, such as gallium oxide, gallium nitrate, indium oxide, indium nitrate, chromium chloride and chromium nitrate, etc.
[0060] According to a preferred embodiment of the present invention, the molar ratio of the structure directing agent R, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is R:SiO2:GeO2:F:H2O=0.15~4:1:0.2~2:0.2~4:12~45; preferably R:SiO2:GeO2:F:H2O=0.5~2:1:0.25~1:0.35~2.5:15~30.
[0061] According to a preferred embodiment of the present invention, the silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane.
[0062] According to a preferred embodiment of the present invention, the germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium.
[0063] According to a preferred embodiment of the present invention, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride, preferably at least one of hydrofluoric acid and ammonium fluoride.
[0064] According to a preferred embodiment of the present invention, the conditions of the crystallization reaction include: crystallization at 100-200°C for 24-300 hours; preferably crystallization at 110-190°C for 36-250 hours, and more preferably crystallization at 155-175°C for 120-220 hours.
[0065] According to a preferred embodiment of the present invention, the crystallization is carried out under static conditions. The preparation method of the UOS molecular sieve provided by the present invention has the advantages of simple organic template structure and high product purity can be obtained without high-speed stirring. In the present invention, the results of static or dynamic crystallization remain basically the same, and the embodiments of the present invention do not specifically describe static or dynamic.
[0066] According to the present invention, after the crystallization reaction is completed, conventional post-treatment is performed, such as filtering, washing, and drying to obtain the molecular sieve; and optionally, a step of calcining the obtained molecular sieve.
[0067] A third aspect of the present invention provides a UOS molecular sieve composition, which comprises the UOS molecular sieve described in the present invention and a binder.
[0068] The present invention has no particular limitation on the binder, and any binder in the art can be used as the binder described in the present invention.
[0069] A fourth aspect of the present invention provides a use of the UOS molecular sieve or the UOS molecular sieve composition of the present invention as an adsorbent or catalyst component.
[0070] In the present invention, in the X-ray diffraction pattern, vw, w, m, s, and vs represent the diffraction peak intensity, vw is very weak, w is weak, m is medium, s is strong, and vs is very strong; generally speaking, vw is less than 5%, w is 5%-20%, m is 20%-40% (including 20% and 40%), s is 40%-70%, and vs is greater than 70% (including 70%).
[0071] In the context of this specification, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source with a Kα1 wavelength of λ=1.5405980 angstroms. Nickel filter.
[0072] In the present invention, an X'Pert PRO X-ray powder diffraction (XRD) instrument of PANalytical Company of the Netherlands is used, with an operating voltage of 40 kV, a current of 40 mA, and a scanning range of 5 to 40°. The product morphology is photographed using an S-4800 field emission scanning electron microscope (Fe-SEM) of HITACHI Company of Japan.
[0073] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) thus formed are part of the original disclosure of this specification and also fall within the scope of protection of the present invention.
[0074] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0075] Example 1
[0076] 5.25g 3-diethylamino-1-propanol (DEAP) was mixed with 10.8g water, and 1.4g germanium oxide was added. After dissolving, 4.0g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour. The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 175℃ oven for crystallization for 144 hours. The solid after the reaction was filtered, washed with distilled water, and dried at 100℃ to obtain the original powder solid. The original powder solid was placed in a muffle furnace and calcined at 550℃ for 5 hours to obtain the final product. The XRD spectrum is as follows: Figure 1 As shown by Figure 1 It can be seen that the product is UOS molecular sieve, the spectrum data is shown in Table 1, and the SEM picture is shown in Figure 2 As shown by Figure 2 It can be seen that UOS molecular sieve is a flaky crystal with a flaky layer thickness of 40 to 350 nm. The nitrogen adsorption-desorption isotherm is as follows: Figure 3 As shown by Figure 3 It can be seen that UOS molecular sieve has a type I isotherm and a specific surface area of 208m 2 / g, micropore volume is 0.08cm 3 / g. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0077] Table 1
[0078]
[0079]
[0080] Example 2
[0081] 5.25g 3-diethylamino-1-propanol (DEAP) and 7.4g water were mixed evenly, 0.84g germanium oxide was added, and after dissolving, 4.8g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature, and finally 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 170℃ oven for crystallization for 168 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final product, and the XRD spectrum was as follows: Figure 4 As shown by Figure 4 It can be seen that the product is UOS molecular sieve, the spectrum data is shown in Table 2, and the SEM photo is shown in Figure 5 As shown by Figure 5 It can be seen that the UOS molecular sieve is a plate-like crystal with a plate thickness of 25 to 450 nm. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0082] Table 2
[0083]
[0084]
[0085] Example 3
[0086] 4.2g 3-diethylamino-1-propanol (DEAP) was mixed with 3.9g water, and 1.4g germanium oxide was added. After dissolving, 4.0g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 1.6g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour. The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 165℃ oven for crystallization for 192 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final UOS molecular sieve product. The XRD spectrum was consistent with Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0087] Example 4
[0088] 5.25g 3-diethylamino-1-propanol (DEAP) was mixed with 7.5g water, 1.9g germanium oxide was added, and after dissolving, 4.0g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature, and finally 2g hydrofluoric acid (40wt%) and 1.35g ammonium fluoride aqueous solution (37wt%) were added, and stirring was continued for 1 hour, and the above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 170°C oven for crystallization for 168 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final UOS molecular sieve product. The XRD spectrum data is shown in Table 3, and the crystal layer thickness is 100-500nm. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0089] Table 3
[0090]
[0091] Example 5
[0092] 3.94g 3-diethylamino-1-propanol (DEAP) was mixed with 5.5g water, and 1.05g germanium oxide was added. After dissolving, 3.3g Ludox silica sol (SiO2 40wt%) and 0.5g white carbon black (SiO2 95wt%) were slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 3.6g ammonium fluoride aqueous solution (37wt%) was added, and stirring was continued for 1 hour. The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 160℃ oven for crystallization for 192 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final UOS molecular sieve product. The XRD spectrum was consistent with Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0093] Example 6
[0094] 7.56g 3-diethylamino-1-propanol (DEAP) was mixed with 9.2g water, and 0.84g germanium oxide was added. After dissolving, 2g Ludox silica sol (SiO2 40wt%) and 1.18g white carbon black (SiO2 95wt%) were slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2g hydrofluoric acid (40wt%) and 1.76g ammonium fluoride aqueous solution (37wt%) were added. After stirring for 1 hour, the above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 170°C oven for crystallization for 168 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final UOS molecular sieve product, and the XRD spectrum was consistent with that of the solid. Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0095] Example 7
[0096] 5.25g 3-diethylamino-1-propanol (DEAP) was mixed with 10.8g water, 1.4g germanium oxide was added, and after dissolving, 4.0g Ludox silica sol (SiO2 40wt%) and 0.36g tetrabutyl titanate were slowly added under stirring, and stirring was continued for 3h at room temperature, and finally 2g hydrofluoric acid (40wt%) was added. After stirring for 1 hour, the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner and placed in a 155°C oven for crystallization for 216 hours. After the reaction, the solid was filtered, washed, dried and calcined to obtain the final Ti-UOS molecular sieve product. The XRD spectrum data is shown in Table 4, and the crystal layer thickness is 35-400nm. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0097] Table 4
[0098]
[0099] Example 8
[0100] 5.25g 3-diethylamino-1-propanol (DEAP) was mixed with 10.8g water, and 1.4g germanium oxide and 0.03g aluminum sulfate 18hydrate were added. After dissolution, 4.0g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour. The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 175℃ oven for crystallization for 120 hours. The solid after reaction was filtered, washed, dried, and calcined to obtain the final Al-UOS molecular sieve product, and the XRD spectrum was consistent with that of the solid. Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0101] Example 9
[0102] 5.25g 3-diethylamino-1-propanol (DEAP) was mixed with 10.8g water, and 1.4g germanium oxide was added. After dissolving, 4.0g Ludox silica sol (SiO2 40wt%) and 0.52g titanium sulfate were slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour. The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 155℃ oven for crystallization for 216 hours. The solid after the reaction was filtered, washed, dried, and calcined to obtain the final Ti-UOS molecular sieve product. The XRD spectrum was consistent with Figure 2 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0103] Example 10
[0104] 5.25g 3-diethylamino-1-propanol (DEAP) was mixed with 10.8g water, and 1.4g germanium oxide and 0.08g aluminum sulfate 18hydrate were added. After dissolution, 4.0g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour. The above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 175℃ oven for crystallization for 120 hours. The solid after reaction was filtered, washed, dried, and calcined to obtain the final Al-UOS molecular sieve product, and the XRD spectrum was consistent with that of the solid. Figure 1 The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.
[0105] Table 5 Example Molecular Sieve Raw Material Molecular Ratio Composition
[0106]
[0107]
[0108] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A UOS molecular sieve, characterized in that: The UOS molecular sieve has a schematic chemical composition as shown in the formula "SiO2·1 / x GeO2", wherein the molar ratio of SiO2 to GeO2 is 0.5≤x≤5, and the UOS molecular sieve has a flaky morphology; The X-ray diffraction spectrum of the UOS molecular sieve includes characteristic peaks as shown in the following table:
2. The UOS molecular sieve according to claim 1, wherein: The molar ratio of SiO2 to GeO2 is 1≤x≤4.
3. The UOS molecular sieve according to claim 1 or 2, wherein: The UOS molecular sieve has a sheet thickness of 20 to 500 nm; and / or The physicochemical parameters of the UOS molecular sieve include: a specific surface area greater than 200 m 2 / g, micropore volume greater than 0.07 cm 3 / g.
4. The UOS molecular sieve according to claim 1 or 2, wherein: No more than 10 wt% of Si atoms in the UOS molecular sieve are replaced by at least one non-silicon tetravalent framework element Y; and / or No more than 2 wt % of the Ge atoms in the UOS molecular sieve are substituted by at least one trivalent framework element X.
5. The UOS molecular sieve according to claim 4, wherein: The Y is selected from at least one of tin, titanium, zirconium and hafnium.
6. The UOS molecular sieve according to claim 4, wherein: 1-9 wt% of Si atoms in the UOS molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y.
7. The UOS molecular sieve according to claim 4, wherein: The X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
8. The UOS molecular sieve according to claim 4, wherein: 0.2-1 wt% of the Ge atoms in the UOS molecular sieve are replaced by at least one trivalent framework element X.
9. A method for preparing the UOS molecular sieve according to any one of claims 1 to 8, characterized in that: The method includes: A step of mixing an optional non-silicon tetravalent framework element Y source and / or a trivalent framework element X source, a silicon source, a germanium source, a fluorine source, a structure directing agent R and water to perform a crystallization reaction to obtain a UOS molecular sieve, wherein the structure directing agent R is 3-diethylamino-1-propanol; The molar ratio of the silicon source calculated as SiO2 to the germanium source calculated as GeO2 is SiO2: GeO2=1: 0.2~2.
10. The preparation method according to claim 9, wherein: The molar ratio of the silicon source calculated as SiO2 to the germanium source calculated as GeO2 is SiO2: GeO2 = 1: 0.25~1.
11. The preparation method according to claim 9, wherein: The molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2 = 0 to 0.1; and / or The Y is selected from at least one of tin, titanium, zirconium and hafnium; and / or The molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.01; and / or The X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.
12. The preparation method according to claim 11, wherein The molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0.01~0.
09.
13. The preparation method according to claim 11, wherein: The molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0.001-0.
005.
14. The preparation method according to any one of claims 9 to 13, wherein: The molar ratio of the structure directing agent R, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is R: SiO2: GeO2: F: H2O = 0.15~4: 1: 0.2~2: 0.2~4: 12~45.
15. The preparation method according to claim 14, wherein: The molar ratio of the structure directing agent R, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is R: SiO2: GeO2: F: H2O = 0.5~2: 1: 0.25~1: 0.35~2.5: 15~30.
16. The preparation method according to any one of claims 9 to 13, wherein: The silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane; and / or The germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium; and / or The fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride.
17. The preparation method according to claim 16, wherein: The fluorine source is selected from at least one of hydrofluoric acid and ammonium fluoride.
18. The preparation method according to any one of claims 9 to 13, wherein: The conditions of the crystallization reaction include: crystallization at 100-200°C for 24-300 hours.
19. The preparation method according to claim 18, wherein: The conditions of the crystallization reaction include: crystallization at 110-190°C for 36-250 hours.
20. The preparation method according to claim 18, wherein: The conditions of the crystallization reaction include: crystallization at 155-175° C. for 120-220 hours.
21. A UOS molecular sieve composition, characterized in that: The composition comprises the UOS molecular sieve as claimed in any one of claims 1 to 8 and a binder.
22. Use of the UOS molecular sieve according to any one of claims 1 to 8 or the UOS molecular sieve composition according to claim 21 as an adsorbent or catalyst component.